Effect of Different Nutrient Solubilizers on the Productivity and Economics of Grain Oat (Avena sativa L.) - Jena, Jagadish; Sarkar, Narayan Chandra; Sen, Chinmoy; Singh, Y. V.; Karmakar, Mrinmoy (International Journal of Bio-resource and Stress Management, 2017)
Oat is one of the important fodder crops widely grown during winter season for grain purpose as well as green fodder in different parts of the World. The experiment was conducted during rabi seasons of 2014-15 and 2015-16 at Agricultural research farm, Institute of Agriculture (Palli Siksha Bhavana), Sriniketan, West Bengal, India for studying the effect of nutrient solublizers combination with on growth, productivity and economics on grain oat. The treatments consists of eleven treatments including absolute control viz., recommended N:P:K:Zn (80:40:40:20 kg ha-1); Azotobacter+75% N+recommended P, K, Zn; Azotobacter+PSB+75% N & P+recommended K, Zn; Azotobacter+PSB+KSB+75% N, P & K+recommended Zn; Azotobacter+PSB+KSB+ZnSB+75% N, P, K & Zn; Azotobacter+KSB+75% N & K+recommended P & Zn; Azotobacter+ZnSB+75% N & Zn+recommended P & K; PSB+KSB+75% P & K+recommended N & Zn; PSB+ZnSB+75% P & Zn+recommended N & K; KSB+ZnSB+75% K & Zn+recommended N & P. The experiment , was laid out in randomized block design (RBD) with each treatment replicated thrice.The results revealed that application of Azotobacter+PSB+KSB+ZnSB+75% N, P, K & Zn exhibited highest dry matter, number of panicles m-2, grain yield, straw yield and biological yield of oat grain production. This was closely followed by other treatments with biofertilizers.The highest gross return, net return and return rupee-1 investment in oat grain cultivation were achieved from the same treatment followed by Azotobacter+PSB+KSB+75% N, P & K+recommended Zn.